Answer:
b. x^2 +2cx +bc+ac-ab = 0
Step-by-step explanation:
It's a matter of what I would describe as tedious algebra. You have to multiply by the least common denominator, then simplify to standard form.
After multiplying the equation by (x+a)(x+b)(x+c) and subtracting the right side, you have ...
(x +b)(x +c) +(x +a)(x +c) -(x +a)(x +b) = 0
Expanding each factor pair gives ...
(x² +(b+c)x +bc) +(x² +(a+c)x +ac) -(x² +(a+b)x +ab) = 0
Collecting terms gives ...
x²(1 +1 -1) +x(b+c +a+c -a -b) +(bc +ac -ab) = 0
x² +2cx +bc +ac -ab = 0 . . . . . matches selection B